Climate and structurally controlled Markandeya River Basin, Belgavi District, Karnataka, India delineated through Morphometry and Hypsometry: A GIS and remote sensing approach - Herlekar, Milind A.; Wadke, Abhishek; Dagade, Ganesh; Gawali, Pravin (My University, 2020)
Morphometry and hypsometry analyses are important tools in planning and developing management programs for river basins, soil and water conservation and natural resources management of river basins. These tools were used to evaluate the climate and structural control over Markandeya river basin (MRB) of northern part of Karnataka state, India. The basin stretches over Kaladgi Super group of rocks, Deccan Traps and laterites. The present paper evaluates morphometric parameters viz., linear, aerial and relief aspects of MRB by Geographical Information System (GIS) and Remote sensing techniques. The MRB is a structurally controlled basin, which has been delineated into 30 sub-basins. Majority of the sub-basin has low drainage density, reveals most of the rainfall infiltrates into the ground. In MRB all 3rd, 4th, and 5th order sub-basins have been coarse and very coarse texture, except Bellarinala which has a fine texture. The computed value of form factor, circularity and elongation ratio suggests that the MRB has elongated in shape and flatter peak flows for longer duration. Hypsometric analysis carried out using 30m ASTER DEM revealed nine sub basins are early youth geomorphic stage; and four sub-basins of late youth stage are influenced by neotectonic activities. Ten sub-basins are approaching early mature stage, and five sub-basins late mature stage. These fifteen sub-basins are experiencing more erosion; these sub-basins are lying within tropical climate zone. The MRB shows old or monadnock stage. The denudational history is understood through basin relief, revealing sub-basins of moderate to high relief.
Keywords: Morphometry; Hypsometry analysis; GIS; Remote Sensing; Markandeya River Basin